FAKTOR-FAKTOR YANG MEMPENGARUHI FERTILITAS DI JAWA BARAT - Hadiyanto, Ferry (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112)DO - 10.24843/bse.2017.v22.i01.p04, 2017)
The purpose of this study is to determine the factors that influence Fertility in West Java. Source of data used in this research is from Indonesan Family Life Survey (IFLS) year 2000 and 2007. This research use descriptive and quantitative analysis and an econometric model with logit approach with female on child-bearing age and the use of contraception for Family Planning (KB) as variables. The most important results of this study indicate that the factors that influence positively Fertility in West Java is the higher level of head of household education and the amount of household members. Meanwhile, the negative influence is indicated by the household head variable. Who work, as well as household expenditures for the upper middle income. Found also, that the use of short-term contraceptive tool was a lot of influence on the community city while long-term contraceptive devices are chosen by women who are getting older.